Deduction of the Concept of ‘Vitality’ in Hegel’s Philosophy - Minkov, Ivo (Wydział Filozoficzny UAM, 2025)
In Hegel’s philosophy, the dialectic of life is based on the expedient course of the concept. This contribution sets itself the task of conducting a hermeneutical and historical-critical reconstruction of the foundation of Hegel’s speculative-dialectical method. The aim is to reveal the philosophical genesis of the concept of ‘vitality’ and its interrelation with spirit. In such a perspective, the idea of the emergence of living matter, which is opposed to the processes of decomposition in the universe, is proposed. The hypothesis here offers a treatment of negative entropy (negentropy) in terms of Hegel’s speculative-dialectical methodology and the spiritual force of the concept that resists the decay of matter. Within such a philosophical conceptualisation arises the concept of vitality, which clarifies the relation between the form of consciousness that a subject can achieve and the energy it will expend to build and structure such a form of consciousness. Of interest is the result that the infinite growth of vitality simultaneously achieves absolute spiritualisation.
Keywords: Hegel; Speculative-dialectical Methodology; Self-consciousness; Dialectic of Life; Vitality; Absolute Spirit.